Osteogenesis Imperfecta: An Uncommon Association with Non-Communicating Hydrocephalus - Chatterjee, K; Dolui, S; Das, S; Paul, A (Journal of Nepal Paediatric Society, 2013)
Osteogenesis imperfecta (OI) is a generalised disorder of connective tissue presenting with fragile bones, blue sclera and early deafness. Hydrocephalus is usually associated with type 2 OI. Here we present a rare case of noncommunicating hydrocephalus and patent foramen ovale in type 3 OI. DOI: http://dx.doi.org/10.3126/jnps.v33i1.6692 J Nepal Paediatr Soc. 2013;33(1):63-65